(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: In today’s world there is an imbalance in the intestinal bacteria. Sedentary lifestyle and poor sleeping schedule have affected our entire body. Apart from that we are regularly consuming unhealthy diets which are low in fiber and high in processed foods and added sugar. Intake of probiotics will be led to the development of intestinal immune system which regulates the intestinal bacteria. Objectives: To check the awareness and knowledge of the Food & Beverage Instructors working in Hospitality Institutions/colleges/universities about probiotic beverages and to check the need of incorporating the concept of probiotics in the curriculum of the hospitality students. Methodology: To fulfill the objective of this research paper we used both primary and secondary data. Numbers of respondent were 77. The respondents were Food and Beverage department instructors working at different Institutes of Hotel Management across India. For primary data collection, a structured questionnaire was designed and sent to Food and Beverage instructors/trainers/lecturers/teachers in the hospitality institutes. Percentage Analysis was done for the calculation of data. Results: The faculty members are very well aware about the concept of probiotic beverages. The results clearly state that not much attention has been paid to the concept as most of the faculty members have not taken theory and practical classes on this topic. However, they intend to take this concept in the future. Conclusion: It can be concluded that despite the knowledge that the faculty members have, for probiotic beverage more attention needs to be given on teaching the concept of probiotic to the hospitality students as due to the current scenario customers are more inclined towards the beverages which along with satisfying their palate provides nutritional benefits to them.